Effects of Heat Stress on Production Performance, Redox Status, Intestinal Morphology and Barrier-Related Gene Expression, Cecal Microbiome, and Metabolome in Indigenous Broiler Chickens - Liu, Wen-Chao; Pan, Zi-Yi; Zhao, Yue; Guo, Yan; Qiu, Sheng-Jian; Balasubramanian, Balamuralikrishnan; Jha, Rajesh (Frontiers in Physiology, 2022)
This study was done to evaluate the effects of heat stress (HS) on production performance, redox status, small intestinal barrier-related parameters, cecal microbiota, and metabolome of indigenous broilers. A total of forty female indigenous broilers (56-day-old) were randomly and equally divided into normal treatment group (NT group, 21.3 ± 1.2 °C, 24 h/day) and HS group (32.5 ± 1.4 °C, 8 h/day) with five replicates of each for 4 weeks feeding trial. The results showed that the body weight gain (BWG) of broilers in HS group was lower than those in NT group during 3-4 weeks and 1-4 weeks (P < 0.05). The HS exposure increased the abdominal fat rate (P < 0.05) but decreased the thigh muscle rate (P < 0.01). Besides, broilers in HS group had higher drip loss of breast muscle than NT group (P < 0.01). Broilers exposed to HS had lower total antioxidant capacity (T-AOC) in serum and jejunum, activities of total superoxide dismutase (T-SOD) in the jejunum, glutathione peroxidase (GSH-Px) in the thigh muscle, duodenum, and jejunum; and catalase (CAT) in breast muscle, duodenum, and jejunum (P < 0.05). Whereas the malondialdehyde (MDA) contents in breast muscle, duodenum, and jejunum was elevated by HS exposure (P < 0.05). Moreover, the relative mRNA expression of Occludin and ZO-1 in the duodenum, Occludin, Claudin-1, Claudin-4, ZO-1, Mucin-2 in the jejunum, and the Claudin-4 and Mucin-2 in the ileum was down-regulated by HS exposure (P < 0.05). The 16S rRNA sequencing results showed that the HS group increased the relative abundance of Anaerovorax in the cecum at the genus level (P < 0.05). Cecal metabolomics analysis indicated 19 differential metabolites between the two groups (P < 0.10, VIP > 1). The Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis revealed that the differential metabolites mainly enriched in 10 signaling pathways such as the Citrate cycle (TCA cycle) (P < 0.01). In summary, chronic HS exposure caused a decline of productive performance, reduced antioxidant capacity, disrupted intestinal barrier function, and negatively affected cecal microbiota and metabolome in indigenous broilers.